Cross-cultural differences in crossmodal correspondences between basic tastes and visual features - Wan, Xiaoang; Woods, Andy T.; van den Bosch, Jasper J. F.; McKenzie, Kirsten J.; Velasco, Carlos; Spence, Charles (Frontiers in Psychology, 2014)
We report a cross-cultural study designed to investigate crossmodal correspondences between a variety of visual features (11 colours, 15 shapes, and 2 textures) and the five basic taste terms (bitter, salty, sour, sweet, and umami). A total of 452 participants from China, India, Malaysia, and the USA viewed colour patches, shapes, and textures online and had to choose the taste term that best matched the image and then rate their confidence in their choice. Across the four groups of participants, the results revealed a number of crossmodal correspondences between certain colours/shapes and bitter, sour, and sweet tastes. Crossmodal correspondences were also documented between the colour white and smooth/rough textures on the one hand and the salt taste on the other. Cross-cultural differences were observed in the correspondences between certain colours, shapes, and one of the textures and the taste terms. The taste-patterns shown by the participants from the four countries tested in present study are quite different from one another, and these differences cannot easily be attributed merely to whether a country is Eastern or Western. These findings therefore highlight the impact of cultural background on crossmodal correspondences. As such, they raise a number of interesting questions regarding the neural mechanisms underlying crossmodal correspondences.